2000
DOI: 10.1046/j.1365-2168.2000.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Day-case laparoscopic fundoplication for gastro-oesophageal reflux disease

Abstract: Outpatient laparoscopic fundoplication is safe and well tolerated by the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 16 publications
1
60
2
2
Order By: Relevance
“…However, only four [6,[12][13][14] out of the seven studies were truly day-care surgery, as three studies [8,15,16] defined discharge within 24 h after surgery as day-care surgery, when an overnight hospital admission is actually a short hospital stay. Of a total of 61 patients, questioned in two studies [8,14], 45 (73%) would undergo the same procedure in day-care again. This review concluded that LNF in day-care was feasible and safe, but a judgment about patient satisfaction and preference could not be made.…”
Section: Discussionmentioning
confidence: 98%
“…However, only four [6,[12][13][14] out of the seven studies were truly day-care surgery, as three studies [8,15,16] defined discharge within 24 h after surgery as day-care surgery, when an overnight hospital admission is actually a short hospital stay. Of a total of 61 patients, questioned in two studies [8,14], 45 (73%) would undergo the same procedure in day-care again. This review concluded that LNF in day-care was feasible and safe, but a judgment about patient satisfaction and preference could not be made.…”
Section: Discussionmentioning
confidence: 98%
“…As the infrastructure of ambulatory surgery improved, other interventions came to the new day surgery units. New upcoming interventions, among others, are laparoscopic cholecystectomy and Nissen fundoplication, minimally invasive parathyroidectomy, axillary dissection, and laparoscopic adrenalectomy, for which several studies have shown the safety and feasibility [1,4,6,[9][10][11][12][13]. Morbidly obese patients are a distinct patient category with their own surgical and anesthesiologic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Echoing previous smaller series [19,20,[24][25][26], our study has shown that the operation can be successfully performed as a day-case procedure in a well-motivated patient who has GERD, minimal comorbidity and a responsible adult at home. During the 5-year study period, as a result of the proven safety and efficacy, LNFs have been increasingly performed as day cases in our unit.…”
Section: Discussionmentioning
confidence: 72%
“…Trondsen et al [26], amongst the earliest authors to investigate the feasibility of day-case LNF in 2000, reported a 13.5% readmission rate and 2.5% major complications rate, and nearly 20% of their patients would have preferred an inpatient procedure. Despite these results they concluded that day-case LNF was safe and well tolerated, and predicted that more than 95% of LNF could be performed as day cases.…”
Section: Discussionmentioning
confidence: 98%